Design and fabricate a go – kart back suspension system - Mohd Bakeri, Muhammad Syafiq; Mohd Yusof, Ab Aziz (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
This project aims to develop a go-kart rear suspension system that enhances safety, handling, and ride comfort. The main challenge is selecting the optimal suspension type, such as independent or solid axle suspension, while balancing weight, adjustability, and chassis compatibility. The goal is to improve grip and stability, especially on uneven tracks and at high speeds. The approach involves analyzing existing suspension designs, focusing on key factors like balance and weight distribution, and developing a system that is lightweight, easily adjustable, and seamlessly integrates with the go kart frame. Prototypes will undergo real-world testing, while computer simulations will predict performance. Advanced technologies, including lightweight materials and electronic controls for real time adjustments, will be explored to optimize efficiency. Safety remains a priority, ensuring robust components and fail-safe mechanisms are in place.